The Translatability of Culture from Chinese to Spanish: Analysis of A Dream of Red Mansions (Sinología hispánica. China Studies Review, 2024)
In order to demonstrate the translatability of culture from Chinese to Spanish, this research analyzes the Spanish translation of A Dream in the Red Mansions, which is the encyclopedia of traditional cultures of China. This study classifies cultural elements, proposes 14 cultural translation techniques and the difficulties in Chinese-Spanish translatability from the following five aspects: linguistic system, lexical gap, semantic association, national psychology and translation activity. It analyzes the various techniques as well as the faithful and aesthetic effect to deal with the translation of cultural elements in the fields of the natural environment, cultural heritage, social culture and linguistic culture, which will contribute to the improvement of the translation of this great Chinese classic in the Spanish-speaking world.